Impact of Auxins on Vegetative Propagation through Stem Cuttings of Couroupita guianensis Aubl.: A Conservation Approach - Mahipal S. Shekhawat; M. Manokari (Scientifica)
The present study explores the potential of exogenous auxins in the development of adventitious shoots and roots from shoot cuttings of Couroupita guianensis (Nagalingam), a threatened tree. Experiments were conducted to assess the effect of various concentrations of auxins on shoot and root morphological traits of stem cuttings in the greenhouse. Amongst the auxins tested, significant effects on number of shoot buds’ induction and their growth were observed with α-Naphthalene Acetic Acid (NAA) treated nodal cuttings. Cent percentage of the stem cuttings of C. guianensis were rooted and shoots were induced when pretreated with 400 mg L−1 NAA for 5 min. Maximum 79% of stem cuttings responded to pretreatment of 300 mg L−1 indole-3-butyric acid (IBA) for 5 min, and 75% of stem cuttings induced shoots with 400 mg L−1 indole-3-acetic acid (IAA). Presence of at least 5 nodes on stem cuttings was found to be prerequisite for root and shoot induction. About 92% of plants were survived under natural soil conditions raised from the stem cuttings. This is the first report of vegetative propagation of C. guianensis through stem cuttings which could be used for conservation strategy and sustainable utilization of this threatened medicinal tree.